The Effect of Demographic Structure on Carbon Dioxide (CO2) Emissions: Top Emitters Case Study - Nurrahmawati, Bela; Kusumawardani, Deni (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2021)
This study aims to analyze how the demographic structure affects carbon dioxide (CO2) emissions in Top Emitters, namely China, the United States, the European Union (EU-28), India, Indonesia, Russia, Brazil, Japan, Canada, and Mexico. This study uses panel data from ten countries stated in Top Emitters for the period 2000-2014 sourced from the World Resource Institute, World Bank and UNESCO Institute for Statistics. This study uses the Panel Data Regression method with the best model chosen is the Random Effect Model (REM) and four demographic structure variables, namely the dependency ratio, sex ratio, higher education ratio, industrial employment ratio. The results of this study indicate that the dependency ratio, sex ratio, higher education ratio, industrial employment ratio have a significant effect on carbon dioxide (CO2) emissions in Top Emitters. The results of this study are expected to provide policies that can be implemented by the government.Keywords: Demographic Structure, Top Emitters, Panel Data Regression MethodJEL : I25, O15, Q5